2023
DOI: 10.3171/2023.1.jns221743
|View full text |Cite
|
Sign up to set email alerts
|

Promoting diversity in neurosurgery through a virtual symposium

Abstract: OBJECTIVE The rates of women and underrepresented racial and ethnic minority (UREM) students successfully matching into neurosurgical residency are extremely low and do not reflect the makeup of the general population. As of 2019, only 17.5% of neurosurgical residents in the United States were women, 4.95% were Black or African American, and 7.2% were Hispanic or Latinx. Earlier recruitment of UREM students will help to diversify the neurosurgical workforce. Therefore, the authors developed a virtual education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Furthermore, our ability to trend the neurosurgery resident CDI over time indicates that the field has consistently made improvements in overall diversity since 2015. While these findings are positive and indicate the potential efficacy of initiatives to improve diversity such as the multiinstitutional neurosurgery summer scholarship for Black medical students, the Stanford Historically Black Colleges and Universities neurosurgery partnership, and the virtual neurosurgery symposium, [48][49][50] there is no guarantee that these trends will continue without close and thoughtful attention by neurosurgical leadership on an ongoing basis. Unlike gender diversity efforts, racial diversity efforts are being actively blocked in the US via anti-diversity, equity, and inclusion legislation, court actions on admissions policies, and a worsening climate of political polarization with respect to racism.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our ability to trend the neurosurgery resident CDI over time indicates that the field has consistently made improvements in overall diversity since 2015. While these findings are positive and indicate the potential efficacy of initiatives to improve diversity such as the multiinstitutional neurosurgery summer scholarship for Black medical students, the Stanford Historically Black Colleges and Universities neurosurgery partnership, and the virtual neurosurgery symposium, [48][49][50] there is no guarantee that these trends will continue without close and thoughtful attention by neurosurgical leadership on an ongoing basis. Unlike gender diversity efforts, racial diversity efforts are being actively blocked in the US via anti-diversity, equity, and inclusion legislation, court actions on admissions policies, and a worsening climate of political polarization with respect to racism.…”
Section: Discussionmentioning
confidence: 99%
“…39 Consequently, efforts to preliminarily engage prospective URiM healthcare students help build self-confidence, provide exposure to the specialty, and reduce perceived barriers to a neurosurgical career. 40 This was evidenced by the Future Leaders in Neurosurgery Symposium for Underrepresented Students, a seven-hour symposium hosted by Duke University for high school and college students, which featured presentations from preeminent neurosurgeons from across the country. 40 Pre- and postsymposium surveys demonstrated increased participant familiarity with neurosurgery, increased confidence in their ability to become a neurosurgeon, and increased exposure to neurosurgeons from diverse groups.…”
Section: Progress and Implementationsmentioning
confidence: 99%
“…40 This was evidenced by the Future Leaders in Neurosurgery Symposium for Underrepresented Students, a seven-hour symposium hosted by Duke University for high school and college students, which featured presentations from preeminent neurosurgeons from across the country. 40 Pre- and postsymposium surveys demonstrated increased participant familiarity with neurosurgery, increased confidence in their ability to become a neurosurgeon, and increased exposure to neurosurgeons from diverse groups. The American Society of Black Neurosurgeons has also made a significant impact since its inception in 2020, 41 hosting a series of webinars and a mentorship program designed to increase the number of Black students entering the field of neurosurgery.…”
Section: Progress and Implementationsmentioning
confidence: 99%
“…Paired pre-and postsymposium surveys showed that the FLNSUS significantly increased participants' familiarity with the field, confidence in their ability to become neurosurgeons, and exposure to neurosurgeons from diverse backgrounds. 37 Long-term follow-up for participants of these events will yield insight into their impact on influencing the decision to pursue a neurosurgical career.…”
Section: Increasing Minority Representation In Neurosurgerymentioning
confidence: 99%
“…Studies within neurosurgery have demonstrated that minority students interested in neurosurgery are more likely to want to work in underserved areas and with minority populations. 37,45 This past year, the ASBN launched "Neuro Mentoring Matters" in collaboration with the Student National Medical Association. This program promotes longitudinal mentorship between neurosurgical attendings, residents, and students to foster the pipeline to a career in neurosurgery.…”
Section: Research Into Outcomes Of Current Diversity and Equity Ini-mentioning
confidence: 99%